Perception Of The Youth Aged 15 To 24 Years On Sexual Debut, Mitigation Strategies And Associated Health Effects In Homa Bay County, Kenya - Anyango, Getrude Opiyo (JOOUST, 2024)
Sexual debut among the youth in the age group of 15 to 24 has been found to be on the increase globally with an upsurge in the reproductive health and social problems such as teenage pregnancy, Illegal abortions, sexually transmitted infections, HIV/AIDS and early marriages. The above issues inspired me to study sexual debut of the youth in Homa bay County where the fertility rate was 23% compared to national prevalence of 15%. Ndhiwa Sub County had the highest of 33% in the County. This study aimed to determine the perception of the youth aged 15 to 24 years on sexual debut, the mitigation strategies and the reproductive health consequences in Homa Bay County. The study was significant because it involved social and health issues in the welfare of the youth. Determining their perception was to provide insight into the understanding of the youth’s sexual behavior. According to Homa Bay County demographic health survey report of 2019, Ndhiwa Sub County was number one in Teenage pregnancy and early marriage. This informed purposive choice of study site as Ndhiwa Sub County. This was across sectional study design in which quantitative and qualitative techniques were applied. The study population was youths aged 15 to 24 years stratified as single and married. The sample size was 273 and further stratified as 141 females and 132 males. The married youths who participated in the focus group discussion were sampled as 13 of either gender. Data was collected using semi structured questionnaire, interview schedule and focus group discussion guide. Data analysis was done by use of SPSS version 25.The descriptive data was summarized and frequency distributions noted. The perception of the youth on sexual debut was evaluated by inferential statistics of Chi- square test of independence to determine relationships between independent and dependent variables. P <0.05 was considered to be statistically significant. The Qualitative data was thematically grouped and analyzed. The findings showed that 61% of the respondents were involved in social relationships and only 14% talked of sexual relationship. Seventy seven percent of the youths said they mainly get sexual behavior information from the peers while 26% said they get information from the media. The sociocultural factors enhancing sexual debut were reported to be peer influence and aftermath of cultural activities. Ninety four percent of the youths said parents were not discussing sexual debut issues with their children and 89% of the youths said the parents did not accept the vise. Sixty eight percent of the male youths considered sex as ordinary activity for fun. Majority of female youths accepted that the sponsor relationships of sex in exchange of gifts or favor exist but generally the youths did not agree with the practice. The mitigation strategies identified by the youth were: abstinence as per 65%, reinforcement of sex education in school as per 85% and avoidance of negative peer influence as per 36%. The youths perceived that engagement in sexual debut can result in the following consequences: Social consequences reported were: school dropout 31%, early and forced marriage 25% and family rejection 18%. The youths reproductive consequences as Criminal abortion 72%, teenage pregnancy 56%, sexually transmitted infections 35%, family planning 11% and complications during childbirth 53%. As a result of the above 99% of the youth agreed that sexual debut affect their health. The focus group discussion had the same ideas with the interviewed group and mainly strengthened adaptation of positive society norms in the prevention strategies. The study concluded that youths are getting information which does not give life skills and living values which can prevent their engagement in risky sexual behavior. The study recommendation is for the health and education departments to enhance counseling on sexual debut and sex education for positive behavior change which is subjective self-control.
Keywords: early marriages; youth; Sexuality; Teenage pregnancy